Resistance to extinction of human evaluative conditioning using a between-subjects design - Díaz, E.; Ruiz, G.; Baeyens, F. (Cognition and emotion, 2005)
Two experiments were conducted to examine whether the resistance to extinction obtained in evaluative conditioning (EC) studies implies that EC is a qualitatively distinct form of classical conditioning (Baeyens, Eelen, & Crombez, 1995 a) or whether it is the result of an nonassociative artefact ( Field & Davey, 1997 , 1998 , 1999 ). Both experiments included between-subjects control groups in addition to standard within-subjects control conditions. In Experiment 1, only verbal ratings were measured in order to evaluate the effect of postacquisition CS-only exposures on EC whereas in Experiment 2, verbal ratings and postextinction priming effects were measured. The results showed that the EC effects are demonstrable in a between-subjects design and that the extinction procedure did not have any influence on the acquired evaluative value of CSs regardless of whether the verbal ratings or the priming effects were used as dependent variables. The present results provide evidence that EC is resistant to extinction and suggest an interpretation of EC as a qualitatively distinct form of associative learning.